2016
DOI: 10.1080/10410236.2015.1045236
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Online Health Information-Seeking Behavior in China: The Roles of Source Characteristics, Reward Assessment, and Internet Self-Efficacy

Abstract: The outbreak of severe acute respiratory syndrome (SARS) in 2003 marked the explosion of health information seeking online in China and the increasing emergence of Chinese health websites. There are both benefits and potential hazards of people's online health information seeking. This article intended to test part of Wilson's second model of information behavior, including source characteristics and activating mechanisms, and to identify the relationships among perceived access, perceived expertise credibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 36 publications
1
57
0
2
Order By: Relevance
“…It seems to be growing almost exponentially, and perhaps will go beyond searches on breast cancer in the next few years. It is consistent, with several works describing the use of Internet (boosted by higher educational level and the worldwide widespread of mobile phones) as a resource to self-care [25,26]. There is also a close correlation between the level of education—which has grown in Brazil in the last decades [27]—and accesses by Google to issues concerning science and health [28].…”
Section: Discussionsupporting
confidence: 81%
“…It seems to be growing almost exponentially, and perhaps will go beyond searches on breast cancer in the next few years. It is consistent, with several works describing the use of Internet (boosted by higher educational level and the worldwide widespread of mobile phones) as a resource to self-care [25,26]. There is also a close correlation between the level of education—which has grown in Brazil in the last decades [27]—and accesses by Google to issues concerning science and health [28].…”
Section: Discussionsupporting
confidence: 81%
“…Considering the predictive roles of risk perceptions and self-efficacy in health information seeking, it is assumed that individuals consider engaging in online communication behaviors when they individually perceive an infectious disease and/or a societal risk issue, and they are confident in their ability to exert personal control. Previous studies found that perceived risks and self-efficacy predicted selective exposure to online health messages (Hastall and Knobloch-Westerwick 2013) and online health information seeking (Cao et al 2016).…”
Section: Psychosocial Factorsmentioning
confidence: 93%
“…First, the previous studies have seldom simultaneously considered online and offline factors when investigating doctors' behaviors in eHealth [1,2,11,16,35,36]. However, as there are close interactions between online health platforms and offline hospitals [4,7], it is not sufficient to focus solely on motivations provided by online channels.…”
Section: Theoretical Implicationsmentioning
confidence: 99%